Remarkable recapture of a Common Whitethroat Curruca communis almost 19 years after ringing. Issue 2 (3rd July 2019) - Pollo, Roberto; Borgo, Enrico
ABSTRACT: A new longevity record has been registered for the Common Whitethroat Curruca communis, with a bird recaptured in Italy 18 years and 11 months from the date of ringing. This exceeds the previous longevity record by almost 10 years. A comparison is made with records of known longevity for other species of small passerine birds. The possible migratory routes and the total distances travelled by the bird are discussed.